Fatigue surviving, fracture resistance, shear stress and finite element analysis of glass fiber posts with different diameters - Wandscher, Vinicius Felipe; Bergoli, Cesar Dalmolin; Oliveira, Ariele Freitas de; Kaizer, Osvaldo Bazzan; Souto Borges, Alexandre Luiz [UNESP]; Limberguer, Inacio da Fontoura; Valandro, Luiz Felipe (Elsevier B.V., 2015)
This study evaluated the shear stress presented in glass fiber posts with parallel fiber (0) and different coronal diameters under fatigue, fracture resistance and PEA. 160 glass-fiber posts (N=160) with eight different coronal diameters were used (DT = double tapered, number of the post = coronal diameter and W=Wider - fiber post with coronal diameter wider than the conventional): DT1.4; DT1.8 W; DT1.6; DT2W; DT1.8; DT2.2 W; DT2; DT2.2. Eighty posts were submitted to mechanical cycling (3 x 10(6) cycles; inclination: 45 degrees; load: 50 N; frequency: 4 Hz; temperature: 37 degrees C) to assess the surviving under intermittent loading and other eighty posts were submitted to fracture resistance testing (resistance [N] and shear-stress [MPa] values were obtained). The eight posts types were 3D modeled (Rhinoceros 4.0) and the shear-stress (MPa) evaluated using FEA (Ansys 13.0). One-way ANOVA showed statistically differences to fracture resistance (DT2.2 W and DT2.2 showed higher values) and shear stress values (DT1.4 showed lower values). Only the DT1.4 fiber posts failed after mechanical cycling. FEA showed similar values of shear stress between the groups and these values were similar to those obtained by shear stress testing. The failure analysis showed that 95% of specimens failed by shear. Posts with parallel fiber (0 degrees) may suffer fractures when an oblique shear load is applied on the structure; except the thinner group, greater coronal diameters promoted the same shear stresses. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Fiber post; Fracture strength; Mechanical cycling; Finite element analysis; Fractographic analysis